Pelatihan Platform Quizizz Dalam Meningkatkan Daya Saing Mahasiswa Dalam Evaluasi Belajar - Gustiana, Zelvi; M. Arif Rahman; Ega Evinda Putri; T.M Johan (Unity Academy, 2022)
Applications that continue to develop in information technology have a major impact in various fields of life, one of which is in the field of education. The field of education is very demanding of renewal so that it can improve its quality so that it can continue to compete. The resulting students must be able to keep up with the times. Therefore we need a method that is able to balance between students and technology. The use of the Quizizz application is a necessary answer to that. The Quizizz application is able to become a bridge as a learning medium that is able to answer the times in the field of technology. Training on the use of the Quizizz Application for students of the Computer Faculty of Almuslim University showed good results in creating student competitiveness so that they could help the development of education.